USING YOUTUBE FOR PROMOTING STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - Fitri Novia; Rachmanita; Citra Rosmita Sari (Language and Educational Journal, 2024)
The paper sought to explore whether there was a substantial alteration in writing procedure text achievement among seventh-grade students at SMPN 1 Sungai Pinang when utilizing YouTube. All the seventh-grade students from SMPN 1 Sungai Pinang in the academic year 2022/2023 were a population. It took fifty-eight students to become the sample. Two groups were formulated, namely experimental and control. A quasi-experimental design was carried out. Written test in the form of an essay, was reported twice as a pre-test and post-test. Formerly, the students were provided with five topics and crafted a procedure text. The scores were then examined using the t-test. SPSS version 26 was spent to calculate it. The independent sample t-test revealed that t-obtain was greater than t-table. The probability value was less than the alpha value. It caused the null hypothesis to be excluded while the alternative hypothesis was established. Hence, there was a substantial variance in writing performance between students who used YouTube and those who did not